THE PEACEFUL SETTLEMENT OF DISPUTES - FUNDAMENTAL PRINCIPLE OF PUBLIC INTERNATIONAL LAW - Roxana-Mariana POPESCU (Challenges of the Knowledge Society)
Enshrined in the 1970 Declaration, under the name of the principle of peaceful settlement of international disputes, the principle obliges states to settle their disputes by peaceful means, so that peace, international security and justice are not endangered. States must act in good faith and in a spirit of cooperation to reach a swift and just solution based on international law. For this purpose, states can resort to means such as: negotiation, investigation, mediation, conciliation, arbitration, judicial settlement or other peaceful means of their choice, including any settlement procedure agreed upon, prior to the occurrence of a dispute to which they are parties.